Pemanfaatan Kecerdasan Buatan (AI) Generatif untuk Personalisasi Pembelajaran Bahasa Inggris : Tinjauan Pustaka tentang Potensi dan Desain Metodologi: Penelitian - Tiarnita Maria Sarjani Br. Siregar; Tania Valensya Br Sihombing; Dwi Anggina Pasha; Nisya Sazwana Nasution; Alia Fatia Zahra Olii (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to analyze the potential implementation and design a conceptual methodological framework for utilizing Generative Artificial Intelligence (AI) in the context of bilingual English language learning in Indonesia. Stemming from the limitations of the one-size-fits-all learning model in accommodating the diverse proficiency levels and first language backgrounds of students, this study employs a systematic literature review and conceptual analysis as its primary methods, without involving field data collection. The results of the literature synthesis indicate that Generative AI, particularly through its capability to produce content, feedback, and interactive scenarios in real-time, holds transformative potential for realizing personalized learning on a large scale. The research proposes an AI-Based Adaptive Learning Methodology Design that encompasses three main pillars: 1) Rapid Diagnosis and Adaptive Learning Pathway Determination based on students' linguistic data; 2) Creation of Contextual Bilingual Materials (e.g., generating reading texts with controlled difficulty and cognitive assistance translations); and 3) Instant Feedback and Error Correction Systems Tailored to individual error patterns. The implementation of this proposed model is expected to serve as a theoretical guide for the development of language learning platforms that are more effective, inclusive, and relevant to the specific needs of bilingual students.